Automobile test (Clifton Park, NY, 2006)
Technicians seeking certification in any one of the automotive ASE exam areas will benefit from the valuable preparation offered by this newly revised package of test preparation booklets. Each title in this popular series features the most up-to-date ASE task list available, along with practice test questions like those typically seen on an ASE certification exam to help users feel more comfortable and prepared to pass the actual test. Comprehensive coverage includes overviews of each task list topic, including descriptions of the actual repair procedure being discussed, plus ASE test taking strategies and detailed explanations as to why a particular answer is correct or incorrect.
Keywords: Automobiles,Automobiles, Automatic,Máy tự động,Xe ô tô,Xe ô tô; Maintenance and repair,Transmission devices, Automatic,Examinations,Transmission devices, Automatic,Maintenance and repair,Maintenance and repair,Bảo trì và sửa chữa,Bảo trì và sửa chữa,Kiểm tra,Bảo trì và sửa chữa,Thiết bị phát, động cơ